The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/s13073-014-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of somatic mutations in cancer using protein pocket-based prioritization approach

Abstract: BackgroundRecently, a number of large-scale cancer genome sequencing projects have generated a large volume of somatic mutations; however, identifying the functional consequences and roles of somatic mutations in tumorigenesis remains a major challenge. Researchers have identified that protein pocket regions play critical roles in the interaction of proteins with small molecules, enzymes, and nucleic acid. As such, investigating the features of somatic mutations in protein pocket regions provides a promising a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…The distribution is shown in Figure 2B and 2C. We defined the mutations with SIFT scores < 0.95 or PolyPhen-2 score > 0.909 as deleterious mutations based on previous studies (4). We found that phosphorylation site mutations were more likely to be deleterious than non-phosphorylation site mutations when they were evaluated using both SIFT ( P = 1.47×10 −6 , Fisher’s exact test, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution is shown in Figure 2B and 2C. We defined the mutations with SIFT scores < 0.95 or PolyPhen-2 score > 0.909 as deleterious mutations based on previous studies (4). We found that phosphorylation site mutations were more likely to be deleterious than non-phosphorylation site mutations when they were evaluated using both SIFT ( P = 1.47×10 −6 , Fisher’s exact test, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, how to assess the impact of these somatic mutations in the process of tumorigenesis and disease progression is a main challenge. Considering the existing observations that many somatic mutations promote tumorigenesis by rewiring protein signaling networks (3), one potential strategy is to incorporate somatic mutations with the protein structure information and investigate them at functional sites (e.g., phosphorylation sites) (48). Phosphorylation-dependent signaling network is fundamental in cellular physiology and its dysfunction plays a critical role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…66 Our observations on protein allosteric dysregulation by somatic variants (Figure 3) are consistent with those previous studies. 7,65,66 In addition, we further developed a permutation statistical model AlloDriver to focus on identifying disease-associated cancer mutated allosteric proteins at particular function regions, allosteric sites, when analyzing more than 47,000 somatic missense mutations. We identified a series of mutated allosteric proteins that harbor enriched somatic variants at their allosteric sites during our pan-cancer and individual cancer-type analyses.…”
Section: Discussionmentioning
confidence: 99%
“…6 Identifying the variants altering protein function is a promising strategy for deciphering the biological consequences of somatic mutations during tumorigenesis and would provide novel targets for the development of targeted cancer therapies. 7 Receptors are a class of proteins with dual roles in the recognition of a drug or environmental factors and the transduction of these stimuli into cellular responses. Although most studies on receptor function have focused on how ligands modulate receptor signaling pathways by binding to orthosteric sites, receptor conformation and signal transduction can also be regulated by ligands acting on unique allosteric sites.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study explored the role of mutations on tumorigenesis (71) and more recently using a structural genomics based approach (72,73). Our work complements these studies by identifying druggable binding pockets and classifying pockets into whether they occur at enzyme active sites or protein-protein interaction sites.…”
Section: Discussionmentioning
confidence: 99%